Maize production systems, farmers’ perception and current status of maize lethal necrosis in selected counties in Kenya - Faith Njeru; Samuel Mwaura; Paul Mbogo Kusolwa; Gerald Misinzo (All Life, 2022)
Maize Lethal Necrosis (MLN) is a disease of maize reported in Kenya in 2012 that results in yield losses of up to 100%. The epidemiology of MLN is complex as the disease is caused by the synergistic interaction of 2 viruses (Maize chlorotic mottle virus (MCMV) and a potyvirus). In addition, multiple reservoirs and transmission pathways exist for the spread of MLN. The current study was conducted to understand farmers’ maize production practices, their understanding of MLN, and the status of MLN in Kenya. Therefore, a survey of 406 randomly selected farmers was conducted in Bomet, Narok, Kirinyaga, Embu, and Nakuru. To confirm the presence of MLN, maize leaf samples were collected from 18 fields and tested for MCMV and SCMV by molecular techniques. MLN Symptoms observed included chlorotic mottle on leaves, necrosis, and premature plant death. MCMV and SCMV were detected in all the maize growing regions at varying levels of incidence, and severity. Sequence analysis of the partial coat protein genes of randomly selected positive samples of the two viruses showed little variability within the studied isolates and those retrieved from the GenBank. The results indicated that MLN is still prevalent in Kenya with farmers’ planting susceptible varieties.